Karakteristik papan partikel dari limbah pertanian (Characteristics of particle board from agricultural waste) - Achmad Supriadi; Adi Santoso; Fahriansyah Fahriansyah (Kementerian Perindustrian, 2022)
Particleboard is a composite wood that still relies on wood from natural forests. Research on the manufacture of particleboard using ligno-cellulosic fibrous material other than wood namely agricultural waste in the form of bagasse and corn stalks using urea-formaldehyde adhesive has been carried out, aiming to obtain information about the characteritic of the resulting particleboard. Particles from bagasse and corn stalks were dried in an oven to a moisture content of 5%. The particleboard density target was made 0.7 g/cm3, using liquid urea formaldehyde (UF) adhesive, with a pressurization process of 12 kg/cm2 at 140°C for 10 minutes. After being conditioned for 7 days, the particle board was made a test sample. The results showed that the particleboard made of bagasse and corn stalks had a density of 0.64 g/cm3 and 0.67 g/cm3, respectively, including medium density, so that they could be used for space insulation, furniture. The development of thickness, MOR and MOE of the manufactured particleboard is significantly influenced by the type of raw material. Moisture content, density and MOR of bagasse particle board are in accordance with SNI standards, while on corn stalk particle board are water content and density.